Advanced Methods for the Development of Highly Adhesive and Bioactive Nano Titania Coatings on Metal Substrates for Orthopedic and Dental Applications - Mathai , Suja (Current Topics on Chemistry and Biochemistry Vol. 5, 2022)
Materials based on titanium dioxide (TiO2) have shown enormous potential for usage in implants due to their superior physicochemical qualities to facilitate bone regeneration and cell proliferation. The greatest study has been done on this metal oxide because of its outstanding performance in a wide variety of applications, chemical stability, and low cost. This study's objective is to assess TiO2's present use in dental and orthopaedic implants. To increase the adhesion strength and long-term dependability of metal implants, researchers have looked at a variety of deposition techniques for TiO2 coating. The various techniques for depositing TiO2 on metal surfaces are thoroughly examined in this article. The techniques discussed include anodization, the sol-gel method, plasma spray coating, cold spray coating, high velocity oxy-fuel spraying, high velocity suspension flame spraying, pulsed laser deposition (PLD), ion beam deposition (IBD), and magnetron sputtering deposition, as well as electrophoretic deposition (EPD), electrochemical deposition, and biomimetic deposition.